ANALISIS PELAYANAN PASIEN RAWAT JALAN PADA RUMAH SAKIT UMUM DAERAH KABUPATEN SIAK - SRI INDRAPURA - Imran Imran (LPPM Universitas Muhammadiyah Sumatera Barat, 2019)
The Regional General Hospital of Siak Sri Indapura Regency as an institution engaged in the field of health services, must always pay attention and provide the best service for its patients. Services provided can be viewed in terms of service time, accuracy, politeness, and friendliness in providing service, responsibility, completeness, ease of service, variety of services, personal service, comfort in obtaining services and supporting attributes of services provided by the home sick. All these aspects are the main focus of the duties of each employee. Although the expected target is almost reached, for the Regional General Hospital of Siak Sri Indapura Regency, there is no escape from the disappointment or dissatisfaction with the services provided to outpatients. Dissatisfaction felt by outpatients is related to examination appointments that are not fixed according to schedule, diagnoses that are felt to be inaccurate, long waits, employees (nurses) who do not listen to complaints and patients, knowledge, skills that are still felt are still not adequate, and lack of patience in dealing with patients who seek treatment. The problem in this study is what factors influence outpatient services at the Regional General Hospital of Siak Sri Indrapura Regency. The research method used in this study is a descriptive method using qualitative data analysis, as well as data analysis by connecting between the theory and the problem under study.Results of the study were obtained: Factors influencing outpatient patients at the Regional General Hospital of Siak Sri Indrapura Regency were direct evidence, reliability, responsiveness, assurance and empathy. Direct evidence, namely tangible evidence provided in services and facilities available to patients, facilities provided include waiting rooms and equipment that are still incomplete or poorly provided. Reliability, namely the ability to provide promised services promptly, accurately and satisfactorily. In this case the appointment is not as scheduled to the patient, because patients are more likely to wait for the doctor to come for treatment. Responsiveness, namely the desire of staff and employees to help customers and provide responsive service. In this case, although it is easily accessible, the system waiting for service is still felt to be less than optimal for patients. Guarantees, which are guarantees given to patients to provide trust in the services available to patients. Empathy, is a strong sense of caring for the condition or condition of the patient, thus giving the patient a sense of security and calm. Empathy given to patients in the form of knowing patients even though not as a whole, because of the large number of patients so that they cannot be recognized carefully by health workers in the hospital and are always patient in facing patients' complaints Keywords : Tangible (Direct Evidence), Reliability, Responsiveness, Assurance and Empathy